1974
DOI: 10.1115/1.3423424
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between a Circular Inclusion and an Arbitrarily Oriented Crack

Abstract: The plane interaction problem for a circular elastic inclusion embedded into an elastic matrix which contains an arbitrarily oriented crack is considered. Using the existing solutions for the edge dislocations [6] as Green’s functions, first the general problem of a through crack in the form of an arbitrary smooth arc located in the matrix in the vicinity of the inclusion is formulated. The integral equations for the line crack are then obtained as a system of singular integral equations with simple Cauchy ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(98 citation statements)
references
References 9 publications
4
93
1
Order By: Relevance
“…However, it seems that analytical tools describing the crack-void interaction are available only for isotropic plate loaded in tension (see [22][23][24][25] for some examples) and, to the best of authors' knowledge, no solutions have been developed so far for composite DCBs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it seems that analytical tools describing the crack-void interaction are available only for isotropic plate loaded in tension (see [22][23][24][25] for some examples) and, to the best of authors' knowledge, no solutions have been developed so far for composite DCBs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In order to illustrate the points made above we consider an example involving two papers presenting results for normalized stress intensity factors of a matrix crack in the presence of an elastic cylinder: one classic paper by Erdogan, Gupta, and Ratwani [1], and a recent paper by Cheeseman and Santare [2]. In the latter paper the authors validate their algorithm by comparing with results from the former paper.…”
Section: Introductionmentioning
confidence: 78%
“…We simply recompute some results of Erdogan, Gupta, and Ratwani [1] and Cheeseman and Santare [2] using an algorithm based on a pair of integral equations for the crack and inclusion problem developed by Helsing and Peters [3]. The integral equations, number (48) and number (49) in Helsing and Peters, are of Fredholm's second kind with compact operators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general problem of a crack interacting with a particle has been studied analytically both for isotropic materials (see, for example, [11][12][13]) and for anisotropic problems (see, for example, [14]). The most relevant to the study reported here is the paper by [15] where the problem of a crack approaching either a coated or uncoated inclusion was studied.…”
Section: Crack Extension Near a Particlementioning
confidence: 99%